Modification of SnO2 nanotubes with g-C3N4 for superior photocatalytic degradation of toxic dye under visible light irradiations - Kumari, Pooja (My University, 2018)
The industrial and domestic waste water effluents from any sources include organic chemicals and pathogens; have maximum pollutants, which can be removed before discharging into water bodies. One of the major water contaminated pollutant has been measured as Rhodamine B. Such pollutant is leading in surface water and groundwater. It will cause irreversible hazards to human and aquatic life in present era. Nanotechnology plays a main role in degrading such type of pollutant. In order to fulfill today’s requirement, we have decided to handle the eco-friendly green synthesis of nanoparicles and its application by merging important fields like environmental sciences, chemical sciences and biotechnology. Here our work emphasizes on the single step synthesis of SnO2/ C3N4 nanoparticles and it was confirmed by various physicochemical characterization techniques such as UV-Visible spectroscopy, XRD, TEM, SEM and BET surface area. This nano-composite showed the excellent photocatalytic activity that is 97 % and making it promising photocatalysts for degradation of dyes.
Keywords: Rhb; SnO2; g-C3N4; UV; NPs